Perspectives of Caregivers on Access to Health Care for Children with CKD - Chandana Guha; Rabia Khalid; Kylie-Ann Mallitt; Anita van Zwieten; Anna Francis; Siah Kim; Armando Teixeira-Pinto; Martha Aquino; Amelie Bernier-Jean; David W. Johnson; Deirdre Hahn; Donna Reidlinger; et al. (Kidney International Reports)
Introduction: Inequitable access to health care based on demographic factors such as ethnicity, socioeconomic status and geographical location has been consistently found in children with chronic kidney disease (CKD). However, little is known about the perspectives of caregivers on accessing health care. We described caregivers’ perspectives on accessing health care for children with CKD from socioeconomically disadvantaged backgrounds and/or rural or remote areas. Methods: Caregivers of Australian children aged 0 to 16 years, across all CKD stages, from low socioeconomic status backgrounds, and/or residing in rural or remote areas, purposively sampled from 5 centers, participated in semi structured interviews on accessing health care. Transcripts were analyzed thematically. Results: From 32 interviews, we identified 6 themes: lack of agency undermining ability to seek care (obscurity of symptoms, uncertain and confused about care processes, and vulnerable and unable to advocate), losing trust in clinicians (confused by inconsistencies and ambiguities in advice, and distressed by lack of collaborative care), exasperated by organizational rigidity (frustrated by bureaucratic roadblocks, lack of access to specialist care in rural and remote settings, and inadequacies of support programs), compounding burden of caregiving (unsustainable financial pressure, debilitating exhaustion, and asymmetry of responsibility), intensifying strain on family (uprooting to relocate, sibling stress and neglect, and depending on family support), building resilience and stability (empowerment through education and confidence in technical and medical support). Conclusions: Caregivers of children with CKD from disadvantaged backgrounds feel disempowered and vulnerable when accessing care for their child. Strategies are needed to improve access to health care for families who are socioeconomically or geographically disadvantaged.